2006
DOI: 10.1357/002224006778715720
|View full text |Cite
|
Sign up to set email alerts
|

Does the marine biosphere mix the ocean?

Abstract: Ocean mixing is thought to control the climatically important oceanic overturning circulation. Here we argue the marine biosphere, by a mechanism like the bioturbation occurring in marine sediments, mixes the oceans as effectively as the winds and tides. This statement is derived ultimately from an estimated 62.7 TeraWatts of chemical power provided to the marine environment in net primary production. Various approaches argue something like 1% (.63 TeraWatts) of this power is invested in aphotic ocean mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 43 publications
5
115
0
1
Order By: Relevance
“…First, Dewar et al [2006] provide an estimate of the global power input to biogenic mixing and show that it is comparable with the power inputs to physical oceanographic mixing processes like wind and tidal forcing. The present results suggest that an important next step is to further segregate this global estimate according to the contributions of vertically-migrating and non-migrating animals, since the former group can achieve significantly more efficient diapycnal mixing than the latter.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…First, Dewar et al [2006] provide an estimate of the global power input to biogenic mixing and show that it is comparable with the power inputs to physical oceanographic mixing processes like wind and tidal forcing. The present results suggest that an important next step is to further segregate this global estimate according to the contributions of vertically-migrating and non-migrating animals, since the former group can achieve significantly more efficient diapycnal mixing than the latter.…”
Section: Discussionmentioning
confidence: 98%
“…[2] The proposition that swimming animals can influence large-scale ocean mixing and circulation was introduced in jest by Munk [1966Munk [ , also personal communication, 2007, but has received more serious attention in recent years [Huntley and Zhou, 2004;Dewar et al, 2006]. Kunze et al [2006] observed significantly elevated kinetic energy dissipation rates in the vicinity of aggregations of krill, and subsequently noted shear fluctuations at length scales up to one meter, significantly larger than the individual animals [Kunze et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…These roles include the regulation of the settling flux of organic and inorganic carbon to the deep ocean and determining levels of reactive trace gases and aerosols in the atmosphere as well as proxy tracers for the carbon cycle such as O 2 , 13 CO 2 and O 18 O. The biodiversity also contributes to variability in physical processes in the ocean, including temperature, stratification and mixing (Dewar et al, 2006;Le Quéré et al, 2005).…”
Section: Plankton Biodiversity Functional Groups and Ocean Biomesmentioning
confidence: 99%
“…In a different approach, on the basis of global estimates of primary production and different methods for quantifying the flux of the produced chemical energy into mechanical energy at higher trophic levels by animal swimming, Dewar et al (2006) also concluded that the marine biosphere may contribute to mechanical energy in the aphotic ocean at a rate comparable with wind and tidal inputs.…”
mentioning
confidence: 99%